Leveraging Question Answering to Understand Context Specific Patterns in Fact Checked Articles in the Global South - Arya, Arshia; Dash, Saloni; Akbar, Syeda Zainab; Pal, Joyojeet; Sen, Anirban (COMPASS 2022, 2022)
Propagation of misinformation on various social media platforms is a common occurrence, especially around political events, religious beliefs, and public health. Fact checked articles, which investigate the credibility of dubious claims online, provide a reliable source of debunked misinformation. However, existing (older) fact checked articles remain an underutilized resource for understanding patterns in fake stories. We propose the use of Question Answering (QA) for analysing fact checked articles for systematically extracting metadata, potentially useful for downstream tasks such as misinformation detection, using a range of simple to nuanced questions. We find that the method gives us a context-specific understanding of common patterns and themes in misinformation, which is especially important in the Global South, where misinformation is layered with propagandist underpinning. Our findings suggest that this method can be extended by fine tuning on any event specific data set of fact checked articles to yield more robust and accurate results.